Wall and Piles for Hydroocarbon Pipes in Soft Soil in Slope Areas - Mutadi Mutadi; Pratikso Pratikso; Abdul Rochim (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Pipes laying on an unstable slope of soft soil are prone to movement. Pipelines that are buried in unstable slope areas will move due to lateral loads from soil movement which can cause damage to the pipeline. A laboratory small-scale model of the reinforcement system of piles supported retaining walls was conducted to investigate the effect of lateral load on the reinforcement. In this experiment, the lateral forces of 0.3 kN, 0.35 kN, and 0.4 kN and vertical force of 0.05 kN, 0.1 kN, and 0.15 kN were used. Lateral load from electric jack is equipped with load cell and vertical load used cement- steel box. To validate the experimental result, a finite element program was used. The experimental results showed that an increase in lateral loading, increased the displacement of the reinforcement system. For a Vertical Load 0.05 kN and versus a lateral load of 0.3 kN causes a horizontal displacement of 0.34 mm and an increased of 2.94 % for loading of 0.35 kN and an increased of 8.82% for loading 0.4 kN. The pattern is the same in the finite element method analysis, where there was a 2.3 8% increased for 0.35 kN loading and an increased to 33.33 % for 0.4 kN loading. In the same Load, the Reinforcement System is reliable as shown in Safety Factor on dry condition were 3,33, 2,828 and 2,476, and on wet condition were 2,99, 2,524 and 2,237.